State-Dependent Entrainment of Prefrontal Cortex Local Field Potential Activity Following Patterned Stimulation of the Cerebellar Vermis - Tremblay, Stéfanie A.; Chapman, C. Andrew; Courtemanche, Richard (Frontiers in Systems Neuroscience, 2019)
The cerebellum is involved in sensorimotor, cognitive and emotional functions through cerebello-cerebral connectivity. Non-invasive cerebellar neurostimulation has been used to treat neurological disorders and has positive effects on cognition and mood related to modulation of frontal EEG oscillations. Here we studied the effects of different frequencies of cerebellar stimulation on oscillations and coherence in the cerebellum and prefrontal cortex in the urethane-anesthetized rat. Local field potentials were recorded in the right lateral cerebellum (Crus I/II) and bilaterally in the prefrontal cortex (frontal association area, FrA) in adult male Sprague-Dawley rats. Stimulation was delivered to the cerebellar vermis (lobule VII) using single pulses (0.2 Hz for 60 s), or repeated pulses at 1 Hz (30 s), 5 Hz (10 s), 25 Hz (2 s), and 50 Hz (1 s). Effects of stimulation were influenced by the initial state of EEG activity which varies over time during urethane-anesthesia; 1-Hz stimulation was more effective when delivered during the slow-wave state (Stage 1), while stimulation with single-pulse, 25 Hz, and 50 Hz showed stronger effects during the activated state (Stage 2). Single-pulses resulted in increases in oscillatory power in the delta and theta bands for the cerebellum, and in frequencies up to 80 Hz in cortical sites. 1-Hz stimulation induced a decrease in 0-30 Hz activity and increased activity in the 30-200 Hz range, in the right FrA. 5-Hz stimulation reduced power in high frequencies in Stage 1 and induced mixed effects during Stage 2. 25-Hz stimulation increased cortical power at low frequencies during Stage 2, and increased power in higher frequency bands during Stage 1. Stimulation at 50 Hz increased delta-band power in all recording sites, with the strongest and most rapid effects in the cerebellum. 25-Hz and 50-Hz stimulation also induced state-dependent effects on cerebello-cortical and cortico-cortical coherence. Cerebellar stimulation can therefore entrain field potential activity in the FrA and drive synchronization of cerebello-cortical and cortico-cortical networks in a frequency-dependent manner. These effects may contribute to therapeutic effects of cerebellar stimulation by promoting large-scale synchronization of neural networks.